Item response analysis of a shortened German version of the morningness–eveningness scale. (21st October 2015) - Jordan, Pascal; Terschüren, Claudia; Harth, Volker
Abstract : A shortened version of the German adaptation of the morningness–eveningness scale of Horne and Östberg is analysed within a large sample of 994 physicians with respect to dimensionality, reliability, gender differences and validity. The psychometric analysis – which incorporates a highly robust method to check for unidimensionality – shows discrepancies towards unidimensionality and highlights three misfitting items. In addition, hypothesis testing indicates the presence of differential item functioning (DIF) with respect to gender which could be caused by differences in response formats. Although, reliability estimates are satisfactory, an overall lack of adequate psychometric properties of the scale within the population of physicians has to be reported. We derive suggestions for improvement of the original morningness–eveningness questionnaire (MEQ)-scale and provide general comments on how to check for unidimensionality without imposing a restrictive response model.